Fetal abnormality with possibility of legal termination: maternal dilemmas - Samira de Souza Patrício; Vitória Regina Petters Gregório; Silvana Maria Pereira; Roberta Costa
ABSTRACT Objective: To identify maternal dilemmas about the diagnosis of fetal abnormality incompatible with life. Method: The exploratory-descriptive qualitative method was used. Eight women participated in the research between September/2016 and January/2017 through semi-structured interviews. The data were analyzed from the thematic analysis together with the ATLAS.ti software. Results: The experiences of this study were based on suffering and emotions. The termination choice was based on personal factors of women and families, such as information on pathology and religion. Diagnoses of incompatible fetal abnormalities bring the most different feelings to those involved. It is extremely important to establish a clear communication between woman, family and interdisciplinary team in the course of gestation and delivery, with elucidation about prognosis and therapeutic possibilities. Final considerations: It was visualized the importance of embracement, communication and treatment given by the multiprofessional health team.